2008
DOI: 10.1086/524662
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Hospital-Acquired Urinary Tract Infection in the United States: A National Study

Abstract: Despite the strong link between urinary catheters and subsequent UTI, we found no strategy that appeared to be widely used to prevent hospital-acquired UTI. The most commonly used practices--bladder ultrasound and antimicrobial catheters--were each used in fewer than one-third of hospitals, and urinary catheter reminders, which have proven benefits, were used in <10% of US hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
165
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 30 publications
4
165
0
1
Order By: Relevance
“…Unfortunately, as of a 2005 survey, most hospitals do not systematically track urinary catheter insertions and removals. 8 The above concerns are highlighted for surgical patients among whom indwelling urinary catheter use is particularly high. In a 2001 sample of Medicare beneficiaries, 85% of major surgical patients had perioperative urinary catheters.…”
mentioning
confidence: 99%
“…Unfortunately, as of a 2005 survey, most hospitals do not systematically track urinary catheter insertions and removals. 8 The above concerns are highlighted for surgical patients among whom indwelling urinary catheter use is particularly high. In a 2001 sample of Medicare beneficiaries, 85% of major surgical patients had perioperative urinary catheters.…”
mentioning
confidence: 99%
“…Some of these included nurse-driven approaches such as automatic stop orders, nurse-driven protocols to remove IUCs that failed to meet speciic checklist criteria and nurse-driven physician reminders [29]. Other programs were physician focused with IUC renewals as a required daily order or documentation of continued indication as a required part of the daily patient note [30,31].…”
Section: Remembering the Forgoten Iuc (Quality Improvement)mentioning
confidence: 99%
“…In Michigan, the Keystone Bladder Bundle [34]. A nationwide survey of 470 hospitals revealed that CAUTI incidence decreased by 25% in Michigan hospitals and by 6% in non-Michigan hospitals during the same period [29]. A big component of the success of this initiative was due to the appointment of "champions" that were responsible for addressing individual questions and encouraging continued engagement in the reduction of catheter use [23].…”
Section: Remembering the Forgoten Iuc (Quality Improvement)mentioning
confidence: 99%
See 1 more Smart Citation
“…UTI is the most common bacterial infection (4) and one of the most prevalent hospital-acquired infections, with economic repercussions, sequelae, complications and immeasurable harm to the population. It represents about 40% of all hospital-acquired infections and 70% to 88% of them are caused by the use of catheters (5)(6)(7) . In intermittent catheterization, the catheters are removed shortly after emptying the bladder, which is associated with lower UTI rates, while indwelling catheters are connected to a urine collector, which increases the risk of infection (2,8) .…”
Section: Introductionmentioning
confidence: 99%